Hacia una teoría Latinoamericana de las ciencias sociales del desarrollo - García , Antonio (1973)
One of the most dangerous and widespread myths of the social sciences consists in the belief that social-scientific theory is absolutely universal and that its validity goes beyond the framework of cultural spaces and historical processes. Of course, this myth is most dangerous from the point of view of backward and dependent countries in the particular case of economic science, insofar as it relates to the problems of wealth, property, income distribution, accumulation and investment, subtly hiding its ideological background in the various forms of scientific rationalization.